Correlations between omega-3 fatty acids and inflammatory/glial abnormalities: the involvement of the membrane and neurotransmitter dysfunction in schizophrenia - Zhang, Yongping; Yin, Jingwen; Yan, Haifeng; Yan, Ling; Li, Yuyu; Zhang, Cai; Li, Yajuan; Liu, Baiping; Lin, Juda; Zhang, Liqiang; Hu, Xueqiong; Song, Cai (Frontiers in Cellular Neuroscience, 2023)
Macrophages or T-lymphocytes triggered inflammation, and consequently activated glial cells may contribute to neuroinflammation and neurotransmitter dysfunction in schizophrenia (SZ). While omega(n)-3 polyunsaturated fatty acids (PUFAs) can attenuate some SZ symptoms though antiinflammatory effects. However, the correlations between macrophages/T-lymphocytes-produced cytokines and glia phenotypes, between inflammatory status and PUFAs composition, between cytokines and neurotransmitter function, and between n-3 PUFAs and neurotransmitter abnormality in SZ are unclear. Changes in T helper (h) patterns, peripheral macrophage/glial markers, PUFAs profile, membrane fluidity and neurotransmitter functions were evaluated in SZ patients (n=50) and healthy controls (n =30) by ELISA, gas chromatography, fluorescence anisotropy techniques and HPLC respectively. Compared to the control, blood lymphocyte proliferation, the concentration of macrophage/microglia phenotype M1 markers, including cytokines IL-1 TNF- h and IL-6 (Th2) and astrocyte phenotype A1 marker S100 were significantly increased, while IL-17 and n-3 PUFAs contents, n-3/n-6 ratio, and membrane fluidity (FLU) were significantly decreased in SZ.Moreover, increased DA and HVA, decreased 5-HT, NE and their metabolites appeared in SZ.Moreover, negative correlations between IL-6 and A2 marker BDNF or n-3 PUFAs EPA, between IL-1 and FLU or 5HIAA, while positive correlations between EPA and 5-HIAA and between FLU and DHA were found in SZ. These findings showed 1) no clear Th pattern, but pro-inflammatorydominant immunity occurred; 2) the pro-inflammatory pattern may result in activated microglia M1 and astrocyte A1 phenotype; 3) increased pro-inflammatory cytokines were related with decreased n-3 PUFA, decreased membrane fluidity and dysfunctional neurotransmitter systems in SZ.